2019
DOI: 10.1109/jphot.2019.2903223
|View full text |Cite
|
Sign up to set email alerts
|

Super-Fast Refresh Holographic Display Based on Liquid Crystal Films Doped With Silver Nanoparticles

Abstract: Holography as a true three-dimensional (3-D) technique is thought to be the ultimate display technique. However, dynamic holographic materials still have problems such as slow refresh, high applied electrical field, etc., to be solved to realize video-rate 3-D display. We present silver nanoparticles (Ag NPs) doped liquid crystal films with very big birefringence and super-fast hologram refresh speed as real-time dynamic holographic medium, which can be applied in holographic video display. And the fastest res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…High-resolution transmission and reflection holographic gratings written in polymeric materials are known and investigated for a long time [1,2], and cover a large variety of applications, ranging from high density data storage [3][4][5], to lasing [6,7], to super-fast holographic displays [8]. More recently, all optically addressable holographic gratings have been also widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution transmission and reflection holographic gratings written in polymeric materials are known and investigated for a long time [1,2], and cover a large variety of applications, ranging from high density data storage [3][4][5], to lasing [6,7], to super-fast holographic displays [8]. More recently, all optically addressable holographic gratings have been also widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Holographic three-dimensional (3D) display can rebuild both the intensity and phase information of real 3D scene, so holographic 3D display is regarded as a true 3D display technology and has been widely concerned [1]. With the development of computer technology, computer-generated holography (CGH) has become a research hotspot, and CGH has great application prospects in medical treatment [2,3], spatial cognition and navigation [4], education [5], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Li et al [12] employed a mixture of nematic LC (5CB) and quantum dots (Zns/InP) to a rise time as short as 6.4 ms, but the decay time was 140 ms. In 2019, Gao et al [13] reported 5CB doped with silver nanoparticles to obtain 50% diffraction efficiency at a recording beam power of 0.1 mW mm -2 . However, diffraction efficiency declined rapidly to 7% with the increase of recording power.…”
Section: Introductionmentioning
confidence: 99%